Mobile-based employee presence application development at PT.visionet International data - Aulia Alfina Rahmadanti; Syahrizal Dwi Putra (Journal of Engineering, Technology and Computing (JETCom), 2022)
Employees are one of the most important assets for the company. With employee satisfaction with the company, it is possible for employees to provide the best for the company. Attendance attendance is an important role in every job where attendance is one of the main supports that can support and motivate every work activity carried out in it. Currently the company PT. Visionet Data Internasional is still running the attendance system using manual attendance, namely by using manual paper. This can result in several errors starting from data collection and calculation of attendance hours, hours out, to information not coming in, this has an impact on the relatively long time in the process of calculating attendance recapitulation from employees, as well as the form of attendance reports made in the form of hard copies. can cause errors in data recording, complicate the data search process and it can be feared that there will be loss of employee attendance data. By using the Mobile Application, employees only need attendance via smartphone. In this study, the method used is the waterfall method using Unified Modeling Language (UML) modeling. Then this application is designed using Android Studio and MYSQL. This application is designed with the aim of making it easier for employees to take attendance.